1995
DOI: 10.1002/cjce.5450730517
|View full text |Cite
|
Sign up to set email alerts
|

A model for simultaneous measurement of gas and solid holdups in a bubble column using ultrasonic method

Abstract: The ultrasonic method developed to measure the dispersed phase holdups in dispersion systems is based on the fact that the velocity of ultrasound in the dispersion is different from that in the liquid. The relationships between velocity differences in the term of transmission time differences of ultrasound and gas holdup in a gas‐liquid system and solid holdup in a liquid‐solid system were derived. The holdups became linearly dependent on the time differences, which is in agreement with the experimental data. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…The change in amplitude (or attenuation) and acoustic velocity of a mixture depend on density, particle size and applied frequency. Warsito et al (1995) applied the ultrasonic technique to gasliquid and liquid-solid systems. Soong et al (1995) and Stolojanu and Prakash (1997) applied the ultrasonic technique to three phase slurry systems to measure solids concentration.…”
Section: Ultrasonic Techniquementioning
confidence: 99%
“…The change in amplitude (or attenuation) and acoustic velocity of a mixture depend on density, particle size and applied frequency. Warsito et al (1995) applied the ultrasonic technique to gasliquid and liquid-solid systems. Soong et al (1995) and Stolojanu and Prakash (1997) applied the ultrasonic technique to three phase slurry systems to measure solids concentration.…”
Section: Ultrasonic Techniquementioning
confidence: 99%
“…This is however contrary to the observations made by others including Macchi et al (2001), Vatanakul et al (2003) and, Zheng and Zhang (2004). The success of Warsito et al (1995) model could be due to the low gas velocities (< 0.03 m/s) used in their experiments. Vatanakul et al (2003) have demonstrated that the fluctuations in acoustic velocity are effected by the phase hold ups.…”
Section: Introductionmentioning
confidence: 59%
“…Chang et al (1984) have reported a good relationship between phase holdup and attenuation. The change in acoustic velocity due to gas phase has been investigated by various researchers (Warsito et al, 1995;Soong et al, 1995;Macchi et al, 2001;Vatanakul et al, 2003;and Zheng and Zhang, 2004). The model suggested by Warsito et al (1995) relates transit time change in GLS systems with individual phase holdups using the following relationship:…”
Section: Introductionmentioning
confidence: 99%
“…The total organic carbon of the solutions was measured using a total organic carbon analyzer (Shimadzu TOC-500). The radius of resonance bubbles generated by the gas sparger was investigated by measuring the sound velocity using the method described elsewhere [7]. Fig.…”
Section: Experimental Equipment and Methodsmentioning
confidence: 99%